Analisis Faktor yang Berhubungan dengan Kinerja Bidan dalam Memberikan Pelayanan Antenatal Berkualitas Diwilayah Kerja Puskesmas Kota Bukittinggi Tahun 2018 - Khairan Nisa; Joserizal Serudji; Delmi Sulastri (Universitas Batanghari Jambi, 2019)
Quality antenatal care has a major role in reducing maternal mortality. Every effort to improve quality must also be accompanied by efforts to pay attention to factors that contribute to improving the performance of midwives in providing services. The study used a combination of quantitative approaches in 67 midwives in the Bukittinggi and qualitatively in 15 informants, of which 9 people included in-depth interview informants to coordinator midwives, head of the Public health center and staffing and 6 FGD informants to midwives on duty at the health center.The results of quantitative data analysis, factors related to the performance of midwives are incentives, motivation and workload. Motivation is the most dominant factor related to the performance of midwives. The results of qualitative data analysis, the leadership plays an important role in increasing motivation to work midwives and optimizing the role of midwives in overcoming problems related to overlapping workloads. Midwives also need to increase their participation efforts and empower pregnant women so that programs can run well and provide positive feedback for improving the health status of pregnant women. Basically antenatal services provided by midwives are in accordance with standards, but the paradigm of antenatal care for pregnant women must shift from achieving quantity to focus on quality. To improve the performance of midwives in providing antenatal care, several efforts are needed: monitoring and evaluation of the quality of antenatal care by midwives, leadership involvement in efforts to increase midwife motivation both from supervision and reward management in non-material forms. Providing equal opportunities for midwives to improve competence through training, especially training related to quality antenatal care. In addition, the provision of infrastructure at the polindes needs attention.